(untitled) (World Bulletin of Public Health, 2022)
In recent years, there has been a steady increase in the incidence of malignant neoplasms in all major localizations. Unfortunately, there remains a high percentage of tumors detected in stage 4 of the process in the presence of distant metastases, incl. bone metastases. Despite the improvement in diagnostic methods, the frequency of detection of osteogenic multiple metastases in prostate cancer (PC) and renal cell carcinoma (RCC) is one of the most urgent problems of modern oncourology. Skeletal metastases are very devastating for patients with renal cell carcinoma, leading mainly to osteolytic lesions that disrupt the integrity of the bone and adversely affect the outcome of the disease. Skeletal involvement in RCC is associated with skeletal events including pain, nerve compression , hypercalcemia , and even pathological fractures that may require surgery and other therapy. Although bone turnover markers are not definitive in the diagnosis of skeletal metastases, they can be very useful in monitoring patients with known primary cancers for bone metastases.